Combination of laser welding with in-mould assembling into a single process - Oliveira, N. (2014)
The search of a process capable of produce and assemble complex subsystems in a short period is the goal of any company. In the market it is possible to found several solutions. They go from simple glue to the complexes systems that use moulds, robot and other. These systems are part of a complex assembling line. In these lines are several different processes as welding, plastic and assembling process. This complex structure is costly, and in countries where the labour cost is high. To maintain the cost the companies are obliged to go overseas. The process presented had the objective of reducing the complexity of an assembling line. The reduction of the complexity is achieved through the combination of the in-mould assembly and the laser welding. The in-mould assembly is used to produce in the same mould several components. Laser welding is used to join different polymers. To study the viability of the process I was chosen a case study, in this case, a rear lamp. Firstly, it was modified to this new process, and then each component was studied individually. Finally, all the processes were combined and it was concluded that this process has viability and to make it possible producing a complex subsystem in one process.